PTU-159 Self reporting of gluten sensitive GI symptoms in primary care: should we accept the diagnosis of coeliac disease without further investigations?. (28th May 2012) - Aziz, I; Evans, K E; Newrick, L; Sanders, D S
Abstract : Introduction: Many unselected patients presenting to gastrointestinal (GI) clinics self-report that they have symptoms related to the ingestion of gluten. For this reason we undertook a prospective and systematic evaluation of this group of patients to ascertain the subsequent diagnostic yield. Methods: All patients were referred to a dedicated coeliac or gluten sensitivity clinic by GPs through a choose and book system. The referral criteria were "GI symptoms attributed to gluten ingestion." Investigations included baseline haematology, biochemistry, haematinics, C reactive protein and HLA status for the DQ2/DQ8 haplotypes. In addition, coeliac serology was performed: endomysial antibody (EMA), tissue transglutaminase antibody (tTG), immunoglobulins, as well as duodenal biopsies on a gluten containing diet. A diagnosis of coeliac disease was based on either the presence of villous atrophy or in cases with lesser degrees of the modified Marsh grading, an associated positive coeliac serology and/or HLA typing. Results: 140 patients were investigated over a 5-year period. 80% were women and the median age of presentation was 37 yrs (range 16–88). In patients self-reporting symptoms related to the ingestion of gluten, the diagnosis of coeliac disease was reached in 10% (n 14). 85% (n 119) did not have coeliac disease but fulfilled the ROME criteria for irritable bowel syndrome (IBS). These patients were given a clinical diagnosis of gluten sensitive IBS (GS-IBS). Importantly, organic pathology was found in 5% (n 7) all of whom had additional alarm symptoms—mesenteric ischaemia, bacterial overgrowth, lactose intolerance, bile salt malabsorption, lymphocytic colitis, ulcerative colitis and pyloric stricture. A positive coeliac serology (p<0.0001, exact fisher test) was significantly associated with coeliac disease. All patients with coeliac disease were HLA positive compared to 44% of GS-IBS cases. There was statistically no significant difference in gender, clinical symptoms or baseline bloods (haemoglobin, vitamin B12, folate, ferritin, calcium or albumin) between the groups, (p>0.05). Conclusion: Self-reporting of gluten related GI symptoms only results in a diagnosis of coeliac disease in 10% of cases. The majority of patients do not have overt coeliac disease but may belong to the spectrum of GS-IBS, a relatively new and under researched concept. Moreover, 5% had significant underlying disease. An empirical trial of gluten-free diet prior to referral may be unhelpful and delay the diagnosis in this group of patients. This data suggests that patients who self-report gluten induced GI symptoms should be considered for further investigations. Competing interests: None declared.